Control Rod Drop Hydrodynamic Analysis Based on Numerical Simulation - Cheng, Jie; Wang, Zhenying; Lu, Chuan; Zhang, Jibin; Bi, Shumao; Feng, Qilong (Frontiers in Energy Research, 2020)
The drop time of the control rod plays an important role in judging whether a nuclear reactor can be safely shut down in an emergency condition and has become one of the most important parameters for the safety analysis of nuclear power plants. Exact assessment of the drop time is greatly dependent on the forces acting on the control rod. In this research, a three-dimensional numerical simulation of the control rod in a low-temperature heating reactor was established based on 6DOF (6 degrees of freedom) model using dynamic meshing technology, and it was used to analyze the control rod dropping experiment. The behavior of dropping the control rod was obtained, including the velocity, the displacement, and the pressure distribution on the control rod guide tube. The comparison between the simulation and the experiment results indicated that the simulation was capable of simulating the dropping characteristic of the control rod. Some important parameters can be calculated, such as the time of control rod dropping process and the maximum impact force. Based on this, useful information could be provided for the design of control rod driveline structure.